Use of a collagen matrix for recession coverage in patients who received orthodontic therapy: a case series. Issue 1 (18th August 2015) - Tan, Wah C.; Tan, Wah L.; Ong, Marianne M.A.; Lang, Niklaus P.
Abstract: Aim: The aim of the present study was to determine the percentage of recession coverage achieved following surgery with a collagen matrix, and patient‐reported outcome measures. Methods: Five healthy adults who had completed orthodontic therapy with a gingival recession defect were recruited. Gingival recession coverage was performed using a two‐layer, xenogeneic collagen matrix (Mucograft). During the first 2 weeks, the patients charted their perceptions on bleeding, swelling, pain, and bruising using a visual analog scale (VAS). Post‐surgical complications were assessed clinically at 1 week, 2 weeks, and 1 month post‐surgery. Recession dimensions were examined at 1, 3, 6, and 12 months. Results: At 1 year, an average of 67% root coverage was achieved. The amount of recession coverage achieved was stable from 3 months. The results were maintained at 1 year. There were no post‐surgical complications. All VAS parameters decreased to almost zero by day 14. From day 1, bleeding and pain decreased over time. However, there were peaks on days 2 and 3 for swelling and bruising, respectively, followed by a subsequent decrease. Conclusions: The use of Mucograft for recession coverage is effective and safe, with low morbidity and no post‐surgical complications. Recession coverage achieved at 3 months remained stable in the 1‐year follow‐up period.